Investigating the impact of perceived stress and anxiety on nonspecific low back pain among future health care professionals in Hungary: a cross-sectional study - Blanka Bernadett Kasza; Blanka Bernadett Kasza; Kinga Nákity; Regina Finta; Norbert Pásztor; Takayuki Kurokawa; Mariann Sápi; Andrea Domján (Frontiers in Psychology)
IntroductionHealth-science students frequently experience low back pain (LBP), influenced by stress, academic demands, and sedentary lifestyles. This study investigated associations between pain intensity, subjective disability, psychological factors (perceived stress and anxiety), LBP-related knowledge, daily sitting hours, and weekly sports participation in health-sciences students. It further examines the link between psychological factors and nonspecific LBP among Hungarian health-science students.MethodsIn total, 172 students (155 women, 17 men, age: 20.33 ± 1.47, Body Mass Index (BMI): 22.32 ± 3.64) participated in the study. 111 subjects (103 women, 8 men, age: 20.52 ± 1.50, Body Mass Index (BMI): 22.48 ± 3.66) had low back pain (LBP group), and 61 subjects (52 women, 9 men, age: 19.97 ± 1.34, BMI: 22.01 ± 3.61) did not (non-LBP group). The Visual Analogue Scale (VAS), Oswestry Disability Index (ODI), Perceived Stress Scale (PSS), State-Trait Anxiety Inventory (STAI), daily sitting hours, weekly sports participation, and Low Back Knowledge Questionnaire (LKQ) were assessed and analyzed as LBP-associated factors.ResultsStress level of the LBP group indicates high perceived stress (PSS: M = 27.23, SD = 8.38), STAI in the complete sample showed “moderate anxiety” (STAI-S: M = 43.30, SD = 9.75; STAI-T: M = 40.33, SD = 11.43) with a significant difference of STAI-T (p = 0.003) between groups. In both groups, a significant, strong positive correlation was found between perceived stress and anxiety (LBP STAI-S: rs = 0.67, p = 0.000; LBP STAI-T: rs = 0.74, p = 0.000; non-LBP STAI-S: rs = 0.66, p = 0.000; non-LBP STAI-T: rs = 0.73, p = 0.000). trait anxiety showed a statistically significant positive association with pain intensity (β = 0.264, SE_β = 0.120; b = 0.051, SE_b = 0.023; p = 0.031), and ODI also had a significant positive correlation (β = 0.731, SE_β = 0.052; b = 0.438, SE_b = 0.031; p < 0.001). No relationship was found between the sitting hours and the other variables of the study in either group.DiscussionThis study found a significant association between trait anxiety and personal experiences of LBP in Hungarian health science students. No link was found between LBP and daily sitting hours or sports participation. Given the high prevalence of stress and anxiety among future healthcare professionals and their established link to LBP, health science curricula should include comprehensive education on the psychosocial aspects of LBP.Clinical trial registrationClinicalTrials.gov, identifier NCT05487729 (04/08/2022).